(untitled) - Gere, James M. (Australia, 2004)
Now featuring the problem-solving CD-ROM, StressAlyzer, the Sixth Edition of this book continues its tradition as the leading text in Mechanics of Materials. With its hallmark clarity and accuracy, this text develops student understanding along with analytical and problem-solving skills. The main topics are the analysis and design of structural members subjected to tension, compression, torsion, bending, and more. The book includes more material than can be taught in a single course so instructors have the opportunity to select the topics they wish to cover.
Keywords: Strength of materials